Pengaruh Sosialisasi Perpajakan, Tarif Pajak, Sanksi Pajak Terhadap Kepatuhan Wajib Pajak Kendaraan Bermotor - Nuraisah (Jurnal Akuntansi Keuangan dan Bisnis, 2025)
This research aims to determine the influence of tax socialization, tax rates and tax sanctions on motor vehicle taxpayer compliance. The population in this study was 324,410 motor vehicle taxpayers registered at SAMSAT Depok II Cinere. The data collection technique used was the convenience sampling method so that the sample obtained was 114 taxpayer respondents. The collection method used a Likert scale which was analyzed using the SPSS version 29 program. Based on the results of the Coefficient of Determination test, the adjusted R-Square value was obtained at 0.233. The results of simultaneous test hypothesis testing (f test) show that the influence of tax socialization, tax rates, tax sanctions simultaneously influences motor vehicle taxpayer compliance, this is proven by the significance value of 0.001 which is smaller than 0.05. The results of partial test hypothesis testing (t test) show that variables x1 and x2 have no effect on Y because the calculated r is smaller than the r table, while the x3 variable has a partial effect on variable Y because the calculated r value is greater than the r table.